Harvest timing and potassium doses on post-harvest quality of dwarf-green coconut water - Medeiros Câmara, Francisco Mickael; Pereira, Eduardo Castro; Alves, Anderson Araújo; Pereira, Gustavo Alves; dos Santos, Elizangêla Cabral; Mendonça, Vander (Comunicata Scientiae, 2021)
Coconut is an expressive culture in tropical climate regions and its yield and fruit quality is directly linked to several factors, such as climatic conditions, fertilizer management, harvesting fruits period and other factors. Aiming to evaluate post-harvest of irrigated green dwarf coconut water quality due to potassium doses and different harvesting time, an experiment was carried out at the Federal Rural University of the Semi-Arid - UFERSA from January to November 2015. The experimental design was split-plot randomized blocks. Plots were 5 potassium doses (0, 150, 300, 450 and 600 g plant-1) and the subplots 4 harvesting time of fruits (5, 6, 7 and 8 months after the opening of the inflorescence), 4 blocks and 2 plants for a total of 40 treatment plants. The experimental area consisted of coconut trees of green dwarf variety with four years old. Were evaluated the titratable acidity, soluble solids, ratio, electrical conductivity, pH, total sugar and levels of potassium, calcium, magnesium, sodium and chlorine from coconut water. Under the conditions studied, higher doses of potassium decreased qualitative characteristics of coconut water, the absence of potassium fertilization coconut trees had better results. The optimal harvest time is between 6 and 7 months old.